Kinetic Architecture: Towards the Poetry of Space in Movement - Yılmaz, İrem (ICONARCH International Congress of Architecture and Planning, 2014)
The concept of “Kinetic Architecture” provides an extensive framework for the broad-array of inquiries upon the relationship between movement, human and space. Focusing on the dynamic configuration of physical space via movement in Kinetic Architecture, in this paper it is asserted that in order to understand kinetic spatial embodiments, a new aesthetic conception that goes beyond our conception of static spatial embodiments is needed. Using the conceptual frameworks; Eco’s poetics of the “Work in Movement” in context of his theory of “The Open Work”, Dewey’s theory of “Art as Experience” and Heidegger’s conceptions of “poetry as building” and “poetical measuring” as an explanatory tool, it intends to conceptualize aesthetics of the space in movement. As considering the movement as existential manifestation, poetical building of space in movement is opened to discussion as an alternative way of production of space in relation to aesthetics.